Prevalence and correlates of elder neglect in the community-dwelling Chinese population: New evidence from the CLHLS study - Fu, Yi-cheng; Pei, Min-yue; Liao, Jiao-jiao; Li, Nan; Zhang, Fu-chun; Liu, Hui-lin (Frontiers in Public Health, 2023)
Background: This study aimed to explore the prevalence of elder neglect (EN) and its associated factors among community-based Chinese older adults. Methods: We used data from the 2018 phase of a nationwide cross-sectional study, the Chinese Longitudinal Healthy Longevity Survey (CLHLS), which recruited 15,854 older adults to complete the study interviews that incorporated six dimensions of EN, including life neglect, social isolation, medical neglect, poor living situation, family neglect, and social neglect. Multivariate logistic regression was used to explore factors associated with EN. Results: We included demographic factors, chronic diseases, cognitive function, and daily activity function in our comprehensive analysis, and showed that they had different effects on the six EN dimensions. Different demographic factors such as gender, age, marriage, education, occupation, residence and household income were included in the comprehensive analysis, and the results showed that these factors had different effects on the six dimensions of EN. Second, we found that older adults with chronic diseases are prone to life neglect, medical neglect, and residential environment neglect. Older adults with better cognitive abilities were less likely to be neglected, and a decline in daily activity capacity has been linked to EN in older adults. Conclusion: Future studies are needed to identify the health effects of these associated factors, develop prevention strategies for EN, and improve the quality of life of older adults living in communities.